Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174214
|View full text |Cite
|
Sign up to set email alerts
|

Voice Interfaces in Everyday Life

Abstract: Voice User Interfaces (VUIs) are becoming ubiquitously available, being embedded both into everyday mobility via smartphones, and into the life of the home via 'assistant' devices. Yet, exactly how users of such devices practically thread that use into their everyday social interactions remains underexplored. By collecting and studying audio data from month-long deployments of the Amazon Echo in participants' homes-informed by ethnomethodology and conversation analysis-our study documents the methodical practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
260
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(327 citation statements)
references
References 34 publications
9
260
0
15
Order By: Relevance
“…Research [15,16,20,38,40,44] has consistently identified that humanness is fundamental to speech interface design, supporting the metaphor of human dialogue for interaction. It is currently unclear what dimensions are important in users' conceptualisation of humanness and how people see speech interface functionality through this lens.…”
Section: Discussionmentioning
confidence: 97%
“…Research [15,16,20,38,40,44] has consistently identified that humanness is fundamental to speech interface design, supporting the metaphor of human dialogue for interaction. It is currently unclear what dimensions are important in users' conceptualisation of humanness and how people see speech interface functionality through this lens.…”
Section: Discussionmentioning
confidence: 97%
“…The recent popularity of IPA devices like Amazon Echo and Google Home has generated considerable interest in the HCI community [40,42]. Recent emphasis in HCI has been on understanding user experiences of interactions with IPAs.…”
Section: Conversational Agentsmentioning
confidence: 99%
“…These include checking the weather, setting reminders, calling and messaging, playing music, launching other applications, information seeking, and interacting with Internet of Things (IoT) devices [2,20,35,38,54]. Although these devices promise much through their implied humanness [20], they fall short of the reflexive and adaptive interactivity that occurs in most human-human conversation [42]. Instead interactions revolve around brief question/answer or user-instructions/system-confirmation dialogues [42].…”
Section: Conversational Agentsmentioning
confidence: 99%
See 2 more Smart Citations